PENGEMBANGAN MEDIA PEMBELAJARAN PAKAR (PAPAN & KARTU) SCRABBLE UNTUK PEMBELAJARAN MUFRODAT - Siti Aisyah (Al-Lahjah, 2019)
Arabic is a foreign language that is widely studied in Indonesia. But in learning Arabic, there are so many problems faced by students when learning Arabic. Among the low student interest in learning, there is an assumption that learning Arabic is a difficult thing and the limited learning media of Arabic so learning feels monton and boring. From these problems, researchers developed a learning media in the form of Arabic Hole board games to increase student motivation and facilitate student understanding. The researcher uses a research and development (R&D) approach with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. Conducting small trials and field trials to improve students' learning motivation in class XI at MA Al Bairuny Sambongdukuh Jombang using Arabic Hole media. The results obtained are the influence of the media on students' learning abilities especially in reading skills (Maharah Qira’ah).Learning media has a main role in the teaching and learning process. Problems faced by students will end up using learning media. Problems that occur in class X MA students. Nidzamiyyah, namely, the boring teaching and learning process and the lack of various methods, strategies and learning aids and media. Students find it difficult to memorize vocabulary and pronunciation. This study aims to study the development of learning media "boards and Scrabble cards" for vocabulary learning in class X Madrasah Aliyah Nidzamiyyah Ploso Jombang as well as the validity and practicality of the media. This study used the Research and Development method with the Borg and Gall model. The data collection method was observation. , questionnaires and interviews. The validity results showed in two analyzes. The first was the media validity analysis by two experts and the 4.39 results from the material field 3.93 from the media field. And it shows that this method is very feasible. The second, the practicality analysis by respondents/students and practitioners/teachers. Researchers conducted product trials twice and also the results of questionnaires from teachers. The results obtained 62% in the first experiment (small group) said that mufrodat learning using the media "board and Scrabble cards" was quite good. The results of 78% in the second experiment (large group) said that mufrodat . learning use the media "Scrabble board and cards" very well. While the results from the practitioners/teachers obtained 3.95 that teaching vocabulary using the "scrabble board" learning method is good.